The quality conundrum in higher education - Aisi Li; Alan Ruby (My University, 2018)
Aisi Li and Alan Ruby critically reflect on the persistent challenge of defining and measuring "quality" in higher education amid global trends such as internationalization, student mobility, and the proliferation of branch campuses. They argue that commonly used metrics (e.g. rankings, enrollment numbers) often oversimplify institutional performance and neglect mission-specific excellence. The authors call for more context-sensitive, purpose-driven frameworks that prioritize meaningful learning outcomes over numerical indicators.
Keywords: internationalization; student mobility; branch campus; higher education quality